2014
DOI: 10.1093/jac/dku024
|View full text |Cite
|
Sign up to set email alerts
|

Novel drug combination for Mycobacterium abscessus disease therapy identified in a Drosophila infection model

Abstract: This D. melanogaster-M. abscessus infection/curing methodology may be useful for the rapid evaluation of potential drug candidates. In addition, new combinations using tigecycline and linezolid should be considered as possible next-generation combination therapies to be assessed in higher organisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
33
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 22 publications
0
33
0
Order By: Relevance
“…New nonmammalian models of infection have been developed, including for Drosophila melanogaster (33,34), Caenorhabditis elegans (35), or Danio rerio (36,37), offering advantages in terms of speed, cost, technical convenience, and ethical acceptability over the mouse model. Except for the recent Drosophila model (34), these models have not been reported for antibiotic assessments against M. abscessus.…”
Section: Discussionmentioning
confidence: 99%
“…New nonmammalian models of infection have been developed, including for Drosophila melanogaster (33,34), Caenorhabditis elegans (35), or Danio rerio (36,37), offering advantages in terms of speed, cost, technical convenience, and ethical acceptability over the mouse model. Except for the recent Drosophila model (34), these models have not been reported for antibiotic assessments against M. abscessus.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the past few years the development of multiple cellular, non-mammalian and mammalian models have helped to study the chronology and the pathology of Mabs infection (Byrd and Lyons, 1999; Howard et al, 2006; Ordway et al, 2008; Oh et al, 2013; Bernut et al, 2014a; Bakala N'Goma et al, 2015; Roux et al, 2016). Among these new model systems, a few have been validated for their suitability for in vivo drug efficacy studies against Mabs (Ordway et al, 2008; Lerat et al, 2014; Oh et al, 2014; Bernut et al, 2014b). These different infection models and their applications are discussed below in more details.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding M. abscessus infection, in vitro DST studies demonstrated a low MIC of CFZ and in vitro synergy between CFZ and other antibiotics, such as clarithromycin (CLR), AMK, or tigecycline (23)(24)(25)(26)(27)(28). The antimycobacterial activity of CFZ against M. abscessus was also demonstrated in vivo with Drosophila melanogaster and mouse models of infection (29,30).…”
mentioning
confidence: 97%